Are you still mad? - Weiss, Ellen; Couri, Kathryn A. (Pleasantville, N.Y. : Reader's Digest Children's Books, 1999)
After having a fight, best friends Sonya and Anna decide it is more fun to play than to stay mad at each other.
"Grades 1-2"--cover.
76982
Keywords: Best friends -- Fiction; Friendship -- Fiction; EZ